Greening the economy: How public-guaranteed loans influence firm-level resource allocation - Bruno Buchetti; Ixart Miquel-Flores; Salvatore Perdichizzi; Alessio Reghezza (European Central Bank (ECB), 2024)
This study investigates the underlying reasons for banks' continued support of fossil fuel-based firms and examines the role of public guaranteed loans (PGLs) in redirecting resources towards greener economic activities, thereby facilitating the climate transition process. Using a unique pan-European credit register dataset, we combine supervisory bank data with firm-level greenhouse gas emission data and financial information. Our analysis yields three main findings. Firstly, European banks perceive lending to green companies as riskier compared to their brown counterparts, a phenomenon we term as the "green-transition risk." Secondly, we provide evidence that during the COVID-19 pandemic, European banks have strategically leveraged PGLs to channel resources towards environmentally sustainable activities, thereby augmenting the proportion of green loans in their portfolios and partially shifting the inherent "green-transition risk" to European governments and citizens. Lastly, our investigation reveals a banking preference for awarding PGLs to financially robust green firms over less profitable, highly indebted green firms, which could pose significant challenges for green businesses requiring financial support during the COVID-19 crisis.
Keywords: G20; G21; G28; 330; Climate Change; Green Lending; Public Guaranteed Loans; Credit Risk